PENANA: AUDIO-VISUAL MEDIA TO IMPROVE ACROSTIC POETRY WRITING SKILLS - Abdul Gani, Resyi; Indriani, Rini Sri; Hikmah, Nur (Jurnal Ilmiah Didaktika, 2024)
Interactive learning media strengthens user responses as quickly and often as possible, providing opportunities for students to control their learning pace and pay attention to coherent sequences assisted by audio-visual media penana, which can improve acrostic poetry writing skills. This research was conducted on July 25, 2023, with a total of 24 students consisting of 2 men and 22 women. This study aims to see how writing poetry, acrostic techniques assisted by audio-visual media, and penana applications can improve poetry writing skills using a qualitative approach and a classroom action research design following the Kemmis and Taggart model. The study was conducted in 3 cycles, where each cycle included 4 stages, namely planning, acting, observing, and reflecting, and involved 24 students in semester V. Data was obtained using observation, tests, non-tests, interviews, and documentation. The findings of this study suggest that the acrostic technique of poetry, assisted by audio-visual media, can help improve poetry writing skills. The results showed an increase in semester V students' poetry writing skills. This was evidenced by the classical completeness of the success of Indonesian grammar and literature skills cycle I by 71% with the criteria of "very good," cycle II writing poetry with 53% criteria "good," and cycle III poetry writing skills acrostic techniques by 49% with the "enough" criterion, and understand how to write acrostic technique poems by 60% with the "good" criterion. Also carried out was a multiplication of in-depth information on the ability to write audio-visual rocky acrostic poetry, and the publication of acrostic poetry for the application of penana amounted to 92% of the "excellent" criteria. So, efforts to improve acrostic poetry writing skills assisted by audio-visual media are appropriate for interactive learning to strengthen user responses and improve poetry writing skills